Rancang Bangun Ketel Pala dengan Sistem Water Tube - Nuzuli Fitriadi; Edi Saputra (LPPM Politeknik Aceh Selatan, 2017)
The quality of nutmeg oil is determined by the quality of nutmeg and the use of the refining process technology used. Drying techniques for raw materials and distillation processes which include boiler materials, cooling systems, and boiler designs for distillation affect the yield and quality of the essential oils produced. This steam kettle has been made from Stainless steel A304 with a diameter of 40 cm, height 70 cm and plate thickness of 3 mm. The boiler is also equipped with a manometer and thermometer to control the pressure and temperature in the boiler. Excess pressure is controlled by a pressure safety valve. The boiler was designed with a pressure capacity of 3 bars. The time needed to reach a pressure of 3 bars is 30 to 40 minutes with fuel consumption of 2 sticks of wood. Manufacture of mini nutmeg oil refiner with water tube system capacity of 35 to 50 kg. The time needed for the heating process reaches a pressure of 3 bars between 10-15 minutes and a constant temperature, far more effective when compared to conventional systems. The results of laboratory tests state that nutmeg oil distilled using a water tube steam boiler meets Indonesian National Standards.